2015
DOI: 10.5551/jat.29181
|View full text |Cite
|
Sign up to set email alerts
|

Association of Treatment for Hyperlipidemia with Decreased Total Mortality in Japanese Individuals: the Yamagata (Takahata) Study

Abstract: Aim:To evaluate the effects of treatment for hyperlipidemia on total mortality, we examined the association with adjustments for multiple factors, including those related to general health, such as blood hemoglobin and serum levels of albumin, adiponectin, brain natriuretic peptide, and lipids, using a prospective cohort study of a general Japanese population. Conclusions: Not only antihyperlipidemic drugs used but also selection bias and non-evaluated factors, such as socio-economic status, educational level,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
(24 reference statements)
3
7
0
Order By: Relevance
“…The prevalence of hypertension is similar to the 2010 national values for men and women aged 30 to 69 years reported by the Japanese government (50.8% and 33.7%, respectively) [25]. There are no reported national values for hyperlipidemia prevalence (using the same definition as this study), but our observed prevalence is similar to that reported in the other areas of Japan [2629]. We excluded individuals with diabetes from the present study (33 men, 33 women), but with these individuals the prevalence of diabetes in men and women in our original sample (11.7% and 7.9%, respectively) was similar to the Japanese national values (15.4% and 7.1%, respectively) [25].…”
Section: Resultssupporting
confidence: 87%
“…The prevalence of hypertension is similar to the 2010 national values for men and women aged 30 to 69 years reported by the Japanese government (50.8% and 33.7%, respectively) [25]. There are no reported national values for hyperlipidemia prevalence (using the same definition as this study), but our observed prevalence is similar to that reported in the other areas of Japan [2629]. We excluded individuals with diabetes from the present study (33 men, 33 women), but with these individuals the prevalence of diabetes in men and women in our original sample (11.7% and 7.9%, respectively) was similar to the Japanese national values (15.4% and 7.1%, respectively) [25].…”
Section: Resultssupporting
confidence: 87%
“…Because lowering of serum LDL‐C with standard statin regimens reduces the risk of occlusive vascular events in a wide range of individuals, management of dyslipidemia is essential to improve the outcome of patients with HCV eradication. A recent report discussed the relationship between the risk of coronary heart disease (CHD) and the serum level of LDL‐C in the general Japanese population . In another report, serum levels of LDL‐C ranging from approximately 80 mg/dL to 200 mg/dL were positively associated with the risk of CHD in a Japanese cohort .…”
Section: Discussionmentioning
confidence: 99%
“…However, to interpret the relationship of total cholesterol with all-cause mortality, several issues to be discussed were previously raised 5,6) . A report by Daimon, et al contains these issues 7) . In this editorial, we would like to introduce these topics.…”
Section: See Article Vol 22: 1030-1039mentioning
confidence: 99%
“…Daimon et al reported the relation of treated hyperlipidemia, untreated hyperlipidemia, and nonhyperlipidemia participants with total mortality 7) . They concluded that participants with untreated hyperlipidemia showed a higher risk of total mortality than those with treated hyperlipidemia.…”
Section: See Article Vol 22: 1030-1039mentioning
confidence: 99%